Performance Against Cavity Index and Discharge Coefficient between Broad and Sharp Crested Weirs - Abdulla A. Abo (Polytechnic Journal)
The purpose of this research is examining the performance of rectangular broad and sharp crested weirs in terms of cavity index and discharge coefficient. For this purpose, a computational fluid dynamics CFD code FLUENT is applied. Firstly, the code verified by applies on the experiments work of Hagre et al 1994 the results show excellent agreements between CFD and Hager et al 1994. Secondly the code applied on both broad and sharp crested weirs. The results demonstrate that broad crested weirs have a lower discharge coefficient than sharp crested weirs, implying that broad crested weirs have a lower ability to discharge flow than sharp crested weirs. While the cavity index of a broad crested weir is lower than that of a sharp crested weir, the risk of cavitation is lower for a broad crested weir. Finally, designers should use caution when deciding which type of crest to use in their